A soluble single atom catalyst promotes lithium polysulfide conversion in lithium sulfur batteries. Issue 80 (19th September 2019) - Shi, Zhenpu; Wang, Lan; Xu, Huifang; Wei, Junqiang; Yue, Hongyun; Dong, Hongyu; Yin, Yanhong; Yang, Shuting
Abstract : CoPcCl catalyzed the Li2 S decomposition and enhanced the sulfur utilization remarkably. Abstract : CoPcCl is used as a catalytic electrolyte additive for lithium sulfur batteries under the guidance of theoretical calculations. The electrolyte additive strategy is easier to realize and more effective compared with the fabrication of catalytic host materials. Adding CoPcCl in the electrolyte enhanced the sulfur utilization remarkably.